2016
DOI: 10.1155/2016/6193502
|View full text |Cite
|
Sign up to set email alerts
|

ZnSnS3: Structure Prediction, Ferroelectricity, and Solar Cell Applications

Abstract: The rapid growth of the solar energy industry is driving a strong demand for high performance, efficient photoelectric materials. In particular, ferroelectrics composed of earth-abundant elements may be useful in solar cell applications due to their large internal polarization. Unfortunately, wide band gaps prevent many such materials from absorbing light in the visible to mid-infrared range. Here, we address the band gap issue by investigating the effects of substituting sulfur for oxygen in the perovskite st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 70 publications
1
1
0
Order By: Relevance
“…The S 2p spectrum (Figure d) can also be reasonably resolved into two peaks, located at around 163.2 and 161.8 eV, respectively, which are consistent with two S 2− peaks in metal sulfide . Hence, the obtained S−Sn/S−Zn bonded structure could confirm the formation of ZnSnS 3 crystal, which is consistent with the structure analysis of ZnSnS 3 in literature ,…”
Section: Resultssupporting
confidence: 87%
“…The S 2p spectrum (Figure d) can also be reasonably resolved into two peaks, located at around 163.2 and 161.8 eV, respectively, which are consistent with two S 2− peaks in metal sulfide . Hence, the obtained S−Sn/S−Zn bonded structure could confirm the formation of ZnSnS 3 crystal, which is consistent with the structure analysis of ZnSnS 3 in literature ,…”
Section: Resultssupporting
confidence: 87%
“…Although reports of synthesis of these ternary transition metal chalcogenides have been around for a long time [11], there are still few studies focusing on their optoelectronic properties. eoretical studies have been reported on substitution of oxygen with sulfur [12,13]. Additionally, experimental reactions of perovskite oxides with gaseous H 2 S or CS 2 [14], as well as solid-state reactions have been recently reported as methods of substituting oxygen with sulfur [15,16].…”
Section: Introductionmentioning
confidence: 99%